Pulse Quenching and Charge-Sharing Effects on Heavy-Ion Microbeam Induced ASET in a Full-Custom CMOS OpAmp - Fontana, Andrés (2019)
In this work, charge sharing effects on Analog Single Event Transients are experimentally observed in a fully-custom designed, 180nm CMOS Operational Amplifier by means of a heavy-ion microbeam. Sensitive nodes of the differential stage showed bipolar output transients that cannot be explained by single node collection for the closed loop characteristics of the circuit under test. Layout of these transistors are consistent with charge sharing effects due to deposited charge diffusion. Implementation of linear modeling and simulations of multiple node collection between paired transistors of the input stage showed great coincidence with the obtained experimental waveforms, shaped as bipolar, quenched pulses. These effects are also observed due to dummy transistors placed in the layout. A simple parametrization at the simulation level is proposed to reproduce the observed experimental waveforms. Results indicate that charge-sharing effects should be taken into account during simulation-based sensitivity evaluation of analog circuits, as pulse quenching can alter the obtained results, and linear modeling is a simple approach to emulate simultaneous charge collection in multiple nodes by applying superposition principles, with aims of hardening a design.